Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10163496
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Monocyte Activation, Inflammation, and Microbial Translocation Are Associated with Liver Fibrosis in Alcohol Use Disorder

Abstract: Background: The association between markers of inflammation (interleukin (IL)-6 and IL-10), monocyte activation (sCD163 and sCD14), and microbial translocation (lipopolysaccharide (LPS) and LPS binding protein) and liver fibrosis in patients with alcohol use disorder (AUD) and no overt liver disease is not well established. Methods: We studied patients admitted for treatment of AUD at two hospitals in Barcelona. Advanced liver fibrosis (ALF) was defined as FIB-4 > 3.25. Results: A total of 353 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Increased intestinal permeability and changes in the intestinal microbiome are important features of alcohol-related liver damage (Seitz et al, 2018). In previous studies, we demonstrated that increased levels of plasma markers of inflammation, monocyte activation, and microbial translocation are present in a sizable proportion of patients with AUD admitted for hospital detoxification; these increased levels were associated with advanced liver fibrosis (Fuster et al, 2021;García-Calvo et al, 2020). Fungi are commensals of the human intestine, and fungal dysbiosis appears to play a role in the development of alcohol-related liver damage but has received less attention in the literature than microbial dysbiosis (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Increased intestinal permeability and changes in the intestinal microbiome are important features of alcohol-related liver damage (Seitz et al, 2018). In previous studies, we demonstrated that increased levels of plasma markers of inflammation, monocyte activation, and microbial translocation are present in a sizable proportion of patients with AUD admitted for hospital detoxification; these increased levels were associated with advanced liver fibrosis (Fuster et al, 2021;García-Calvo et al, 2020). Fungi are commensals of the human intestine, and fungal dysbiosis appears to play a role in the development of alcohol-related liver damage but has received less attention in the literature than microbial dysbiosis (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…The following day, blood was drawn to assess hematological and biochemical parameters and hepatitis C virus (HCV) infection. Additional information regarding the admission protocol and methods of HCV detection and sCD163, sCD14, Interleukin (IL)‐6, IL‐10, lipopolysaccharide (LPS), and LPS‐binding protein measurements were previously published (Fuster et al, 2021; García‐Calvo et al, 2020). The inter‐assay and intra‐assay coefficients of variation were <10% for all analyses.…”
Section: Participants and Methodsmentioning
confidence: 99%